Características físico-químicas y determinación de plaguicidas en el agua de la laguna de Gandoca, Limón, Costa Rica - Coll, Marta (2004)
Nutrients and chlorophylls concentrations, as well as salinity, temperature and Secchi disk depth were determined from November 1999 to April 2000, at three stations and two depths, at Gandoca lagoon, Gandoca- Manzanillo National Wildlife Refuge, Limón, Costa Rica. Salinity profiles indicated that the lagoon was a salt wedge estuary with a partially mixed region near the mouth. No processes of eutrophication were found. The distribution and abundance of nutrients and chlorophylls showed a slight influence of continental water and water circulation patterns in the lagoon. A preliminary study was done in order to analyze the presence of 20 organochlorated and organophosphorated pesticides along the Gandoca lagoon in February 2000. None of the pesticides were detected by the analysis of residues from liquid-liquid extractions. The absence of the pesticides may be due to the fact that they did not reach the lagoon or, if they did, they were washed away by the strong rains during the sampling period.